2001
DOI: 10.1515/crll.2001.086
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Berezin-Toeplitz deformation quantization

Abstract: We give a complete identi®cation of the deformation quantization which was obtained from the Berezin-Toeplitz quantization on an arbitrary compact Ka Èhler manifold. The deformation quantization with the opposite star-product proves to be a differential deformation quantization with separation of variables whose classifying form is explicitly calculated. Its characteristic class (which classi®es star-products up to equivalence) is obtained. The proof is based on the microlocal description of the Szego È kernel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
158
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(160 citation statements)
references
References 41 publications
2
158
0
Order By: Relevance
“…Also, we can get smoothness of the canonical form (see Proposition 4.7), since it is the Ricci form of the canonical connection. However, to identify the Berezin-Toeplitz product with an E-product in Theorem 4.9, we need the machinery of formal integrals used by Karabegov and Schlichenmaier [20]. Remark 3.17.…”
Section: Corollary 315 Let X Be a Manifold (Possibly With Boundary)mentioning
confidence: 99%
See 3 more Smart Citations
“…Also, we can get smoothness of the canonical form (see Proposition 4.7), since it is the Ricci form of the canonical connection. However, to identify the Berezin-Toeplitz product with an E-product in Theorem 4.9, we need the machinery of formal integrals used by Karabegov and Schlichenmaier [20]. Remark 3.17.…”
Section: Corollary 315 Let X Be a Manifold (Possibly With Boundary)mentioning
confidence: 99%
“…See, for instance, [2] [16] and references therein. 3 On the other hand, Karabegov [19] studied special formal deformation quantization adapted to the Kähler structure, and he and Schlichenmaier [20] linked the two approaches.…”
Section: Quantizationmentioning
confidence: 99%
See 2 more Smart Citations
“…Karabegov and Schlichenmaier [35] showed that the logarithm of the diagonal value of the weighted Bergman kernel is the Karabegov classifying form of the Berezin quantization. There has been much work on deformation quantization of Kähler manifolds and its applications (see the recent survey [50]).…”
Section: Introductionmentioning
confidence: 99%